Enhancing the Effectiveness of Zakat Management in Developing Countries through Strategic Human Resource Management - Badrudin Badrudin; Deviyantoro Deviyantoro (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates the role of human resource management (HRM) in enhancing the effectiveness of zakat institutions in developing countries. Zakat, as a mandatory form of almsgiving in Islam, has significant potential for poverty alleviation and social equity, yet its impact is often hampered by organizational inefficiencies, talent shortages, and governance challenges. Through qualitative research methods, including semi-structured interviews, focus group discussions, and document analysis, the study identifies key themes such as the integration of Islamic principles into HRM practices, challenges in talent acquisition and development, the impact of digital transformation, and the importance of leadership in zakat management.Findings reveal that while many zakat institutions are striving to align HRM practices with Islamic values, significant gaps remain in areas such as employee training, leadership development, and the adoption of digital tools. The study emphasizes the necessity for standardized HRM frameworks that incorporate ethical considerations, targeted recruitment strategies, and robust training programs to equip employees with the necessary skills. Additionally, it highlights the critical role of effective leadership in fostering a culture of accountability and transparencUltimately, this research underscores the importance of strategic HRM in maximizing the potential of zakat as a tool for social equity and poverty alleviation. The study offers practical recommendations for policymakers, zakat managers, and researchers, aiming to facilitate the development of more effective, transparent, and sustainable zakat institutions that contribute to economic justice in Muslim-majority countries.